Factors Affecting The Micro, Small, and Medium Enterprises (MSME) on Tax Compliance : Online Shop Owners - Jefriyanto Jefriyanto; Masril Masril; Bayu Putra Kurniawan (Program Pascasarjana (S2-Ilmu Manajemen) Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2022)
Objective. The purpose of the study was to determine the effect of tax knowledge on tax compliance with paying income taxes for online shop owners, to determine the effect of tax services on tax compliance with paying income taxes for online shop owners, and to determine the effect of tax services on tax compliance with paying income taxes for online shop owners Research Method. The object of this research is SMEs that use online services, Population in this study are the taxpayer who owns an online shop or MSMEs who open online services in the Sekip sub-district in pekanbaru as many as 47 MSMEs. The sampling technique for this study used a census, because the researchers only chose tax knowledge, tax services and tax sanctions, which only amounted to 39 MSMEs that opened online services in Sekip district. Data analysis technique using multiple linear regression. Results. The results show that tax knowledge affects compliance with paying income taxes for online shop owners, tax services affect compliance with paying income taxes for online shop owners and tax sanctions affect compliance in paying income taxes for online shop owners in Sekip sub-district in pekanbaru. Conclusion. Knowledge of taxes, tax services and tax penalty for MSME in Sekip sub-district especially online shop owners affect compliance in paying income taxes. Hoped that further research can choose a different sample, preferably using more or different research samples and not only on MSMEs that doing online shops so that they can describe the general condition of MSME taxpayers.